Intake, digestibility, performance and carcass characteristics of ewes fed crambe replacing soybean meal in the diet - Rafael Henrique de Tonissi e Buschinelli de Goes; Mayara Mitiko Yoshihara Carneiro; Milene Puntel Osmari; Kennyson Alves de Souza; Raquel Tenório de Oliveira; Charles Jhonnatan dos Santos Souza (Acta Scientiarum. Animal Sciences, 2018)
The use of alternative sources of protein for ruminant can alter productivity and reduce costs in animal production. The aim of this study was to evaluate the performance, apparent digestibility and quantitative characteristics of carcass components of ewes fed increasing levels (0, 50, 100 and 150 g kg-1 dry matter) of crambe crushed in the diets. Twenty-four culling ewes were distributed in a completely randomized design. All animals were kept in a shed, with individual stalls equipped with feeder, drinker and concrete floor covered with rice hulls. The animals received corn silage as roughage and diets were isoenergetic with 700 g kg-1 of TDN. Animals were slaughtered when reached a body condition score of 3.5 points. The dry matter intake (948.53 g day-1) and average daily gain (0.15 kg day-1) were not influenced by the inclusion of crambe crushed in the diet. The crambe crushed increased ether extract digestibility and decreased crude protein intake and digestibility. There was no effect of the levels of crambe crushed on carcass characteristics and non-carcass components but rather a reduction in the cold carcass yield. Total replacement of soybean meal with crambe crushed in the diet for ewes did not alter performance, carcass and non-carcass characteristics.